Analisis Komparatif Strategi Pemasaran dan Bauran Pemasaran Dalam Upaya Meningkatkan Kinerja Pemasaran Pada UMKM Tape Ketan di Desa Tarikolot Kabupaten Kuningan - Juanim, Juanim; Hanna Audie, Reisha (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2025)
This research was appointed based on sales data between Pamella companies higher than Sari Asih companies. The purpose of this research is to find out and analyze 1) Respondents 'responses regarding marketing strategies, marketing mix, and marketing performance of Pamella and Sari Asih sticky rice tapes, 2) Respondents' responses regarding marketing strategies and appropriate marketing mix to improve marketing performance on Pamella sticky tape and Sari Asih. 3) Significant differences between marketing strategy, marketing mix and marketing performance of the Pamella sticky tape company and Sari Asih sticky tape. The research method used in this research is descriptive and comparative methods, with comparative data analysis techniques. The results of the analysis in this study indicate that the marketing strategy, marketing mix and marketing performance there are significant differences between Pamella and Sari Asih companies.